Semen Production Characteristics of Pasundan Bull at Different Body Weight - Anggit Damaratri Lapoliwa; Nurul Isnaini (Agricultural Faculty, 2021)
ABSTRACT. Pasundan cattle is currently proposed as a potential livestock to support national meat self-sufficiency program. However, the information regarding their reproductive performance is still very limited. This study was conducted to evaluate the semen production characteristics of Pasundan bull at different body weight. A total of 178 semen samples which were collected from one Pasundan bull were used in this study. The semen collection was done for 31 months and during this period, the body weight of Pasundan bull was classified into 4 categories, namely 400 kg, 400 to 500 kg, 500 to 600 kg, and 600 kg. The results showed that overall mean semen volume, semen pH, sperm concentration, total sperm, individual sperm motility, total motile sperm, post-thawing sperm motility, recovery rate of sperm motility, and frozen semen production were 5.89 ml/ejaculate, 6.69, 1.04 billion/ml, 6.04 billion/ejaculate, 55.75%, 3.40 billion/ejaculate, 40.91%, 58.20%, and 265.11 doses/ejaculate. The difference in body weight significantly affect semen volume (P=0.001), semen pH (P=0.001), sperm concentration (P=0.043), total sperm (P=0.002), individual sperm motility (P0.001), total motile sperm (P0.001), and frozen semen production (P=0.004). There was no significant effect (P0.05) of body weight on post-thawing sperm motility and recovery rate of sperm motility. In conclusion, the semen production traits of Pasundan bull are improved with the increase in body weight up to 500 to 600 kg and remain stable at the body weight of 600 kg.(Karakteristik produksi semen sapi Pasundan pada bobot badan yang berbeda)ABSTRAK. Sapi Pasundan saat ini diajukan sebagai salah satu ternak potensial untuk mendukung program swasembada daging nasional. Akan tetapi, informasi tentang penampilan reproduksinya masih sangat terbatas. Penelitian ini dilakukan untuk mengevaluasi karakteristik produksi semen sapi pejantan Pasundan pada bobot badan yang berbeda. Sebanyak 178 sampel semen yang dikoleksi dari 1 ekor sapi pejantan Pasundan digunakan pada penelitian ini. Penampungan semen dilakukan selama 31 bulan dan pada periode tersebut, bobot badan sapi pejantan Pasundan diklasifikasikan menjadi 4 kategori yaitu 400 kg, 400 to 500 kg, 500 to 600 kg, and 600 kg. Hasil penelitian menunjukkan bahwa rata-rata volume semen, pH semen, konsentrasi sperma, total sperma, motilitas individu sperma, total sperma motil, motilitas sperma post-thawing, nilai recovery rate, dan produksi semen beku adalah 5,89 ml/ejakulat, 6,69, 1,04 miliar/ml, 6,04 miliar/ejakulat, 55,75%, 3,40 miliar/ejakulat, 40,91%, 58,20%, dan 265,11 dosis/ejakulat. Perbedaan bobot badan memberikan pengaruh terhadap volume semen (P=0,001), pH semen (P=0,001), konsentrasi sperma (P=0,043), total sperma (P=0,002), motilitas individu sperma (P0,001), total sperma motil (P0,001), dan produksi semen beku (P=0,004). Di sisi lain, bobot badan tidak memberikan pengaruh (P0,05) terhadap motilitas sperma post-thawing dan nilai recovery rate. Kesimpulannya, karakteristik produksi semen sapi pejantan Pasundan meningkat seiring dengan peningkatan bobot badan hingga 500 sampai 600 kg dan tetap stabil hingga 600 kg.